Hubungan Adiksi Smartphone dengan Mental Emosional pada Remaja di SMPN 1 Jawilan Kabupaten Serang - Haerani, Beti; Imas Yoyoh; Ika Nurjannah (Journal of Pubnursing Sciences, 2023)
Smartphone addiction is the use of smartphones with a period of more than 7 hours per day so users enjoy to use them for a long time, smartphone addiction can have an impact on development especially in adolescents such as emotional disorders. Research goal: to identify the relationship of smartphone addiction with emotional mental health in teenagers at Junior High School 1 Jawilan. Research method: analytical descriptive quantitative with cross sectional approach. Population: 852 all Jawilan Junior High School students. Sample: 98 respondents in class IX with age criteria of 14-16 years. Sampling technique: probability random sampling. Instrument: spread of Smartphone Addiction Scale questionnaire and Self Reporting Questionnaire-20 with statistical tests using chi square. Results: showed that respondents in the most criteria were age criteria of 14 years as many as 55 respondents (56.1%), female gender criteria as many as 51 respondents (52.0%), high levels of addiction in smartphones as many as 86 respondents (87.8%), emotional mental indicators 74 respondents (75.5%). Chi Square statistical test results with a value = 0.035 or less (<0.05). Conclusion: Showing the Relationship of Smartphone Addiction with Emotional Mentality to Teenagers in Junior High School 1 Jawilan. Suggestion: monitoring the use of smartphones will have an impact on the emotional mental health of adolescents.